Comprometimento metastático do linfonodo sentinela e taxa de subdiagnóstico da biópsia percutânea no carcinoma ductal in situ - Sá, Rafael da Silva [UNIFESP] (2016)
Introduction: Ductal carcinoma in situ (DCIS) is characterized by proliferation of ductal epithelium without invasion through the basement membrane. With the increasing use of mammography, there has been a marked increase in the detection of DCIS. Silverstein et al reported lower positive rate of 1% in patients suffering from DCIS who underwent axillary dissection. However, the axillary evaluation remains a routine in some hospitals. Objective: The main objective of the study was to analyze, retrospectively, the positivity of sentinel node biopsy (SNB) in patients with DCIS and the predictive value of minimally invasive biopsies. Methodology: We review patient's medical records with DCIS in outpatient Mastology of Paulista School of Medicine / Federal University of São Paulo between 2009 and 2013. SNB was performed when mastectomy was planned or when there was ?high risk? for invasion (physical examination or imaging shows a mass lesion highly suggestive of invasive cancer, when the area of DCIS imaging is greater than ?4 cm or high nuclear grade). Results: 125 patients were carriers of DCIS and 69 were subjected to SNB. The mean age was 57.2 years and 71.2% of patients were postmenopausal women. Microcalcifications was the primary lesion in 72%. The core needle biopsy was performed in 68.8% of cases. Histologic underestimation was seen in 22.3% (52.3% invasive carcinoma of no special type, 33.3% microinvasive carcinoma, 9.4% invasive papillary carcinoma and 4.7% invasive lobular carcinoma). The sentinel node was negative in 95.7%. In all cases of SN positive (4.3%) the index lesion was nodular, solid histological pattern of DCIS and the surgery was mastectomy. Conclusion: BLS in women in the core needle biopsy showed DCIS should be discouraged by the low positivity rate, except for cases in which it was indicated mastectomy as surgical treatment. In our institution, the underestimation rate of core needle biopsy in DCIS was high but consistent with the literature.